Economies of Scale and Economies of Scope of Commercial Banks in Malaysia - Hashim, Mohd Padzil (2001)
Commercial banks in Malaysia represent the largest financial institutions in term of assets owned, loans rendered and total deposits. To-date, commercial banks account for about 70 percent of the assets, loans and deposit of all financial institutions in the country. They are considered important because they have contributed significantly in intermediating between the depositors in the financial sector and the borrowers in the real sectors that generate economic growth, besides offering a wide range of financial services. The role of the commercial banks in rendering and facilitating the payments system in the financial and capital markets is particularly important. Thus, without a cost effective and operationally efficient payments system, domestic and foreign economic transactions could not be carried out effectively. Commercial banks are considered efficient and effective if they are able to generate outputs or services at a minimum cost and continuously reap the benefits of economies of scale and scope in the long run.